2012
DOI: 10.9790/3008-0234447
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress by Tartrazine in the Testis of Wistar Rats

Abstract: :The aim is to study the effect of Tartrazine (E102)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…Zn derived from testis tissues that were damaged by irradiation could be accumulated in other organ. This result is in harmony with that of Visweswaran and Krishnamoorthy (2012), who reported that Zn, a remarkable antioxidant, is an essential component of many metalloenzymes, its deficiency results in oxidative stress. On the other hand, γ-irradiation induced significant increase in testicular-Cu content.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Zn derived from testis tissues that were damaged by irradiation could be accumulated in other organ. This result is in harmony with that of Visweswaran and Krishnamoorthy (2012), who reported that Zn, a remarkable antioxidant, is an essential component of many metalloenzymes, its deficiency results in oxidative stress. On the other hand, γ-irradiation induced significant increase in testicular-Cu content.…”
Section: Discussionsupporting
confidence: 76%
“…They play important roles in the catalytic and antioxidant activities of major enzymes. Also, deficiency of these trace elements (Zn & Cu) has been implicated with infertility (Nada et al, 2011 andVisweswaran andKrishnamoorthy, 2012). In the current study, γ-irradiation of rats induced decrease in testicular-Zn content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tartrazine administration for 60 days to male rats reduced testicular concentrations of superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase (Visweswaran and Krishnamoorthy 2012). These synthetic colorants can alter concentrations of zinc, iron, copper and manganese which are all essential cofactors for antioxidant enzymes (Cemek et al 2014;Visweswaran and Krishnamoorthy 2012). Food colourings are also associated with increased immune reactivity which may be another mechanism associated with O&NS (Vojdani and Vojdani 2015).…”
Section: Potential Causes Of Oandns In Adhdmentioning
confidence: 99%
“…In an animal study, the administration of several synthetic food colorants and flavour additives lowered blood and liver concentrations of reduced glutathione, glutathione-Stransferase and superoxide dismutase (El-Wahab and Moram 2013). Tartrazine administration for 60 days to male rats reduced testicular concentrations of superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase (Visweswaran and Krishnamoorthy 2012). These synthetic colorants can alter concentrations of zinc, iron, copper and manganese which are all essential cofactors for antioxidant enzymes (Cemek et al 2014;Visweswaran and Krishnamoorthy 2012).…”
Section: Potential Causes Of Oandns In Adhdmentioning
confidence: 99%